Incorporation of digital business into strategy of a FMCG company - Koštová, Michaela (2017)
Master’s thesis focuses on e-commerce market, which has recorded tremendous growth in recent years. Therefore, the main aim is to create a digital strategy focusing on online shopping journey of Czech customers. This strategy focuses on the consumer goods division of L'Oréal Czech Republic. The theoretical part introduces the history and development of e-commerce, along with the basic types and models of e-commerce. An important part is represented by the analysis of the world's e-commerce market, its advantages and disadvantages for both the company and the final customer. Within the world market, the basic e-commerce trends expected in 2017, are also being studied. Focus is then redirected to the Czech e-commerce market, mainly on the behavior of Czech online consumers. The practical part is devoted to the development of a digital strategy between L'Oréal and its client Beauty e-shop, which focuses on the sale of perfumes and cosmetics. The main output of the practical part is an analysis of the beauty e-commerce market, an audit of Beauty e-shop website and own marketing research on the behavior of Czech online consumers. Based on these three analyzes, new digital strategy of L'Oréal is being developed with a focus on improving customer’s online shopping journey.